Total synthesis of the marine natural product solomonamide B necessitates stereochemical revision - Kashinath, K.; Jachak, Gorakhnath R.; Athawale, Paresh R.; Marelli, Udaya Kiran; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Organic Letters, 2016)
The first total synthesis of the proposed structure of solomonamide B has been achieved. However, the H-1 and C-13 NMR spectral data of the synthesized compound was not exactly matching with that of the natural solomonamide B. This prompted us to revise the originally proposed structure, in particular, the stereochemistry of the nonpeptide part, which was confirmed by its total synthesis. During the course of the synthesis, we have developed an interesting hydroxy group directed Wacker oxidation of internal olefins in a macrocyclic setting.

Overcoming the lack of oral availability of cyclic hexapeptides: design of a selective and orally available ligand for the integrin alpha v beta 3 - Weinmueller, Michael; Rechenmacher, Florian; Marelli, Udaya Kiran; Reichart, Florian; Kapp, Tobias G.; Raeder, Andreas F. B.; Di Leva, Francesco Saverio; Marinelli, Luciana; Novellino, Ettore; Munoz-Felix, Jose M.; Hodivala-Dilke, Kairbaan; Schumacher, Adi; et al. (Angewandte Chemie-International Edition, 2017)
Ahighly systematic approach for the development of both orally bioavailable and bioactive cyclic N-methylated hexapeptides as high affinity ligands for the integrin alpha v beta 3 is based on two concepts: a) screening of systematically designed libraries with spatial diversity and b) masking of the peptide charge with a lipophilic protecting group. The key steps of the method are 1) initial design of a combinatorial library of Nmethylated analogues of the stem peptide cyclo(d-Ala-Ala(5)); 2) selection of cyclic peptides with the highest intestinal permeability; 3) design of sublibraries with the bioactive RGD sequence in all possible positions; 4) selection of the best ligands for RGD-recognizing integrin subtypes; 5) finetuning of the affinity and selectivity by additional Ala to Xaa substitutions; 6) protection of the charged functional groups according to the prodrug concept to regain intestinal and oral permeability; 7) proof of biological effects in mice after oral administration.

From a helix to a small cycle: metadynamics-inspired alpha v beta 6 integrin selective ligands - Di Leva, Francesco Saverio; Tomassi, Stefano; Di Maro, Salvatore; Reichart, Florian; Notni, Johannes; Dangi, Abha; Marelli, Udaya Kiran; Brancaccio, Diego; Merlino, Francesco; Wester, Hans-Juergen; Novellino, Ettore; Kessler, Horst; et al. (Angewandte Chemie-International Edition, 2018)
The RGD-recognizing alpha v beta 6 integrin has only recently emerged as a major target for cancer diagnosis and therapy. Thus, the development of selective, low-molecular-weight ligands of this receptor is still in great demand. Here, a metadynamics-driven design strategy allowed us to successfully convert a helical nonapeptide into a cyclic pentapeptide (6) showing remarkable potency and alpha v beta 6 specificity. NMR and docking studies elucidated the reasons for the high affinity and selectivity of this compound, setting the ground for the rational design of new alpha v beta 6-specific small peptides or even peptidomimetics. In vivo PET imaging studies demonstrated the potential use of 6 for medical applications.

N-Heterocyclic carbene-catalyzed michael-michael-lactonization cascade for the enantioselective synthesis of tricyclic delta-lactones - Mukherjee, Subrata; Ghosh, Arghya; Marelli, Udaya Kiran; Biju, Akkattu T. (Organic Letters, 2018)
Enantioselective synthesis of tricyclic delta-lactones with three contiguous stereocenters has been demonstrated by the N-heterocyclic carbene (NHC)-catalyzed functionalization of benzylic C(sp(3))-H bonds. The NHC-catalyzed reaction of enals with dinitrotoluene derivatives under oxidative conditions proceeds via the chiral alpha,beta-unsaturated acylazoliums and produces the delta-lactones in good yields and excellent diastereoselectivity and enantioselectivity. This mild and atom-economic cascade reaction takes place in a Michael/Michael/lactonization sequence and tolerates a broad range of functional groups.

N-Methylation of isoDGR peptides: discovery of a selective alpha 5 beta 1-integrin ligand as a potent tumor imaging agent - Kapp, Tobias G.; Di Leva, Francesco Saverio; Notni, Johannes; Raeder, Andreas F. B.; Fottner, Maximilian; Reichart, Florian; Reich, Dominik; Wurzer, Alexander; Steiger, Katja; Novellino, Ettore; Marelli, Udaya Kiran; Wester, Hans-Juergen; et al. (Journal of Medicinal Chemistry, 2018)
Specific targeting of the integrin subtype alpha 5 beta 1 possesses high potential in cancer diagnosis and therapy. Through sequential N-methylation, we successfully converted the biselective alpha 5 beta 1/alpha v beta 6 peptide c(phg-isoDGR-k) into a potent peptidic RGD binding aSfil subtype selective ligand c(phg-isoDGR-(NMe)k). Nuclear magnetic resonance spectroscopy and molecular modeling clarified the molecular basis of its improved selectivity profile. To demonstrate its potential in vivo, c(phg-isoDGR-(NMe)k) was trimerized with the chelator TRAP and used as a positron-emission tomography tracer for monitoring alpha 5 beta 1 integrin expression in a M21 mouse xenograft.

Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung

Selective targeting of integrin alpha v beta 8 by a highly active cyclic peptide - Reichart, Florian; Maltsev, Oleg V.; Kapp, Tobias G.; Raeder, Andreas F. B.; Weinmueller, Michael; Marelli, Udaya Kiran; Notni, Johannes; Wurzer, Alexander; Beck, Roswitha; Wester, Hans Juergen; Steiger, Katja; Di Maro, Salvatore; et al. (Journal of Medicinal Chemistry, 2019)
Integrins play important roles in physiological and pathophysiological processes. Among the RGD-recognizing integrin subtypes, the alpha v beta 8 receptor is emerging as an attractive target because of its involvement in various illnesses, such as autoimmune diseases, viral infections, and cancer. However, its functions have, so far, not been investigated in living subjects mainly because of the lack of a selective alpha v beta 8 ligand. Here, we report the design and potential medical applications of a cyclic octapeptide as the first highly selective small-molecule ligand for alpha v beta 8. Remarkably, this compound displays low nanomolar alpha v beta 8 binding affinity and a strong discriminating power of at least 2 orders of magnitude versus other RGD-recognizing integrins. Peptide functionalization with fluorescent or radioactive labels enables the selective imaging of alpha v beta 8-positive cells and tissues. This new probe will pave the way for detailed characterization of the distinct (patho)physiological role of this relatively unexplored integrin, providing a basis to fully exploit the potential of alpha v beta 8 as a target for molecular diagnostics and personalized therapy regimens.

EGCG impedes human Tau aggregation and interacts with Tau - Sonawane, Shweta Kishor; Chidambaram, Hariharakrishnan; Boral, Debjyoti; Gorantla, Nalini Vijay; Balmik, Abhishek Ankur; Dangi, Abha; Ramasamy, Sureshkumar; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
Tau aggregation and accumulation is a key event in the pathogenesis of Alzheimer's disease. Inhibition of Tau aggregation is therefore a potential therapeutic strategy to ameliorate the disease. Phytochemicals are being highlighted as potential aggregation inhibitors. Epigallocatechin-3-gallate (EGCG) is an active phytochemical of green tea that has shown its potency against various diseases including aggregation inhibition of repeat Tau. The potency of EGCG in altering the PHF assembly of full-length human Tau has not been fully explored. By various biophysical and biochemical analyses like ThS fluorescence assay, MALDI-TOF analysis and Isothermal Titration Calorimetry, we demonstrate dual effect of EGCG on aggregation inhibition and disassembly of full-length Tau and their binding affinity. The IC50 for Tau aggregation by EGCG was found to be 64.2 mu M.

HDAC6 ZnF UBP as the modifier of tau structure and function - Balmik, Abhishek Ankur; Chidambaram, Hariharakrishnan; Dangi, Abha; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochemistry, 2020)
Histone deacetylase 6 is a class H histone deacetylase primarily present in the cytoplasm and involved in the regulation of various cellular functions. It consists of two catalytic deacetylase domains and a unique zinc finger ubiquitin binding protein domain, which sets it apart from other HDACs. HDAC6 is known to regulate cellular activities by modifying the function of microtubules, HSP90, and cortactin through deacetylation. Apart from the catalytic activity of HDAC6, it interacts with other proteins through either the SE14 domain or the ZnF UBP domain to modulate their functions. Here, we have studied the role of the HDAC6 ZnF UBP domain as a modifier of Tau aggregation by its direct interaction with the polyproline region/repeat region of Tau. Interaction of HDAC6 ZnF UBP with Tau was found to reduce the propensity of Tau to self-aggregate and to disaggregate preformed aggregates in a concentration-dependent manner and also bring about the conformational changes in Tau protein. The interaction of HDAC6 ZnF UBP with Tau results in its degradation, suggesting either proteolytic activity of HDAC6 ZnF UBP or its role in enhancing autoproteolysis of Tau.

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

N-heterocyclic carbene catalysis exploiting oxidative imine umpolung for the generation of imidoyl azoliums - Das, Tamal Kanti; Madica, Krishnaprasad; Krishnan, Jagadeesh; Marelli, Udaya Kiran; Biju, Akkattu T. (Journal of Organic Chemistry, 2020)
Although NHC-catalyzed umpolung of imines are known, the related reactions under oxidative conditions are limited. Described herein is the two-step process involving the initial formation of aldimines from the corresponding aldehydes and 2-amino benzyl alcohols followed by NHC-catalyzed cyclization proceeding via the imidoyl azoliums under oxidative conditions. The reaction allowed the synthesis of trifluoromethylated 3,1-benzoxazines in good yields and broad scope. The role of NHC in the intramolecular cyclization and preliminary mechanistic experiments are also provided.

Novel cilengitide-based cyclic RGD peptides as alpha nu beta(3) integrin inhibitors - Meena, Chhuttan L.; Singh, Dharmendra; Weinmueller, Michael; Reichart, Florian; Dangi, Abha; Marelli, Udaya Kiran; Zahler, Stefan; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2020)
In this letter, we report a series of five new RGD-containing cyclic peptides as potent inhibitors to alpha nu beta(3) integrin protein. We have incorporated various unnatural lipophilic amino acids into the cyclic RGD framework of cilengitide, which is selective for alpha nu beta(3) integrin. All the newly synthesized cyclic peptides were evaluated in vitro solid phase binding assay and investigated for their binding behaviour towards integrin subtypes. All the cyclic peptides were synthesized in excellent yield following solution-phase coupling strategy. The cyclic RGD peptides 1a-e exhibited IC50 of 9.9, 5.5, 72, 11 and 3.3 nM, respectively, towards a alpha nu beta(3) integrin protein. This finding offers further opportunities for the introduction unusual amino acids into the cyclic peptide framework of cilengitide.
Keywords: Anticancer drugs; Cilengitide; Integrins; RGD cyclicpeptides

Residue-based propensity of aggregation in the Tau amyloidogenic hexapeptides AcPHF6*and AcPHF6 - Dangi, Abha; Balmik, Abhishek Ankur; Ghorpade, Archana Kisan; Gorantla, Nalini Vijay; Sonawane, Shweta Kishor; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (RSC Advances, 2020)
In Alzheimer's disease and related tauopathies, the aggregation of microtubule-associated protein, Tau, into fibrils occursviathe interaction of two hexapeptide motifs PHF*(275)VQIINK(280)and PHF(306)VQIVYK(311)as beta-sheets. To understand the role of the constituent amino acids of PHF and PHF* in the aggregation, a set of 12 alanine mutant peptides was synthesized by replacing each amino acid in PHF and PHF* with alanine and they were characterized by nuclear magnetic resonance (NMR) spectroscopy, circular dichroism (CD), transmission electron microscopy (TEM) and ThS/ANS fluorescence assay. Our studies show that while the aggregation was suppressed in most of the alanine mutant peptides, replacement of glutamine by alanine in both PHF and PHF* enhanced the fibrillization.

[1,3]-Claisen rearrangement via removable functional group mediated radical stabilization - Alam, Md Nirshad; Dash, Soumya Ranjan; Mukherjee, Anirban; Pandole, Satish; Marelli, Udaya Kiran; Vanka, Kumar; Maity, Pradip (Organic Letters, 2021)
A thermal O-to-C [1,3]-rearrangement of alpha-hydroxy acid derived enol ethers was achieved under mild conditions. The 2-aminothiophenol protection of carboxylic acids facilitates formation of the [1,3] precursor and its thermal rearrangement via stabilization of a radical intermediate. Experimental and theoretical evidence for dissociative radical pair formation, its captodative stability via aminothiophenol, and a unique solvent effect are presented. The aminothiophenol was deprotected from rearrangement products as well as after derivatization to useful synthons.

Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Total synthesis, structure elucidation and expanded bioactivity of icosalide A: effect of lipophilicity and ester to amide substitution on its bioactivity - Dangi, Abha; Pande, Bharat; Agrawal, Sonia; Sarkar, Dhiman; Vamkudoth, Koteswara Rao; Marelli, Udaya Kiran (Organic & Biomolecular Chemistry, 2023)
The first total synthesis of icosalide A, an antibacterial depsipeptide that is unique in that it contains two lipophilic beta-hydroxy acids, has been achieved by following Fmoc solid-phase peptide synthesis in combination with solution-phase synthesis. The ambiguity in the absolute stereochemistry of icosalide A has been resolved by synthesizing the reported structures and other relevant diastereomers of icosalides and comparing their NMR data. NMR-based structure elucidation of icosalide A revealed a well-folded structure with cross-strand hydrogen bonds similar to the anti-parallel beta-sheet conformation in peptides and displayed a synergistic juxtaposition of the aliphatic sidechains. 12 analogues of icosalide A were synthesized by varying the constituent lipophilic beta-hydroxy acid residues, and their biological activities against Bacillus thuringiensis and Paenibacillus dendritiformis were explored. Most of these icosalide analogues showed an MIC of 12.5 & mu;g mL(-1) against both bacteria. Swarming inhibition by icosalides was least in B. thuringiensis (8.3%) compared to that in P. dendritiformis (33%). Furthermore, this is the first report of icosalides showing assured inhibitory action (MIC between 2 and 10 & mu;g mL(-1)) against the active stage of Mycobacterium tuberculosis and cancer cell lines such as HeLa and ThP1. This study could help optimize icosalides for anti-TB, antibacterial, and anti-cancer activities.

Integrating 3,4-Dihydro-2H-1,4-oxazine into peptides as a modification: silver triflate-catalyzed cyclization of N-Propargyl N-Sulfonyl amino alcohols for SPPS applications - Patil, Abhijit Ramchandra; Marelli, Udaya Kiran (Organic Letters, 2024)
We present a methodology yielding 3,4-dihydro-2H-1,4-oxazine by cyclization of N-propargyl N-sulfonyl amino alcohols using silver triflate as a catalyst at ambient temperature. Additionally, we showcase the applicability of this methodology in solid phase peptide synthesis (SPPS) to introduce the oxazine heterocyclic ring into short peptides containing serine and threonine. Notably, Rink amide resin supported the on-resin formation of 3,4-dihydro-2H-1,4-oxazine, while 2-CTC resin facilitated the oxazine formation in a one-pot process involving peptide cleavage, deprotection, and subsequent C-O ring formation, thus offering a versatile method for the late-stage modification of peptides.

Macrocyclic peptides derived from AcPHF6*and AcPHF6 to selectively modulate the Tau aggregation - Dangi, Abha; Qureshi, Tazeen; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (Bioorganic Chemistry, 2024)
Ten macrocyclic peptides, each comprising 14 amino acids, were designed and synthesized based on the Tau aggregation model hexapeptides AcPHF6* and AcPHF6. The design took into account the aggregation tendencies of each residue in AcPHF6* and AcPHF6, their aggregation models, while employing peptide-based structural design principles including N-methylation to promote turns and to block hydrogen bond propagation and elongation of the aggregation chain. NMR analysis supported that all these peptides adopted an antiparallel beta-sheet conformation. Self-aggregation studies characterized the aggregation properties of these peptides, identifying two peptides with the highest (P3) and lowest (P8) aggregation tendencies. In cross-aggregation studies with the parent peptides AcPHF6* and AcPHF6, P3 and P8 were found to promote and reduce aggregation, respectively. Furthermore, P3 and P8 demonstrated an enhancement and diminution effect on the aggregation of K18wt, indicating their capacity to modulate aggregation even at the macromolecular level. Thus, the two simple peptides, P3 and P8 selectively exhibit pro- or anti-aggregation effects on PHF peptides and Tau. This study, has thus developed structurally well-defined non-complex peptides, derived from AcPHF6* and AcPHF6, to modulate Tau aggregation as desired, offering applications in Tau model studies and the development of Tau aggregation inhibitors or promoters.
Keywords: Cyclic peptides; Peptide -based drug design (PBDD); Peptide conformation; PHF peptides; Tau Aggregation

Metal-free one-pot domino synthesis of oxazolidinethione derivatives of quaternary amino acids from α-amino esters and aldehydes using CS2 - Shinde, Dinesh R.; Krishna, Gamidi Rama; Marelli, Udaya Kiran (Journal of Organic Chemistry, 2024)
We present a streamlined, metal-free, one-pot domino approach to efficiently synthesize oxazolidinethione derivatives containing substituted quaternary amino acids. This method employs alpha-amino esters, aldehydes, and CS2 under mild conditions, constructing three new bonds (C-N, C-C, and C-O) to produce oxazolidinethione compounds featuring a quaternary center and a beta-hydroxy derivative in high yields. This scalable protocol enables the creation of libraries of biologically significant, intricate amino acid derivatives using amino esters and aldehydes.

Graphene oxide-cyclopentylamine (GO-d-CP) liquid crystals as a novel alignment medium for anisotropic nmr with analyte recovery - Jatheendranath, Sandesh Chickmagalur; Das, Akhi; Deshpande, Sudhindra H.; Nath, Nilamoni; Maier, Walter; Streitferdt, Verena; Marelli, Udaya Kiran (Chemistry—Methods, 2025)
In this study, we present graphene oxide derivatized with cyclopentylamine (GO-d-CP) as a DMSO-compatible liquid crystal alignment medium that is free from any background NMR signal for application in anisotropic NMR. This novel alignment medium facilitates optimal isotropic and anisotropic conditions within a single sample preparation, controlled by sonication, thereby enabling the measurement of anisotropic NMR parameters- residual dipolar couplings (RDC) and residual chemical shift anisotropy (RCSA). GO-d-CP offers several advantages, including ease of synthesis, isolation of solid GO-d-CP as a stable non-hygroscopic material, and maintenance of the anisotropic state stability >30 days, allowing for prolonged and repetitive experiments. Notably, post the analysis it allows for easy recovery of valuable analytes as well as GO-d-CP for reuse, enabling the routine application of anisotropic NMR in structural analysis of small molecules. We demonstrate its efficacy by analyzing the relative stereochemistry of four compounds - estrone, santonin, griseofulvin, and cinmethylin - using anisotropic NMR data.

Ketenimine multicomponent strategy for multifaceted amidine functionalization of peptides on the solid phase - Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Angewandte Chemie-International Edition, 2025)
The amidine group and its derivatives serve as proteolytically stable bioisosteres of the peptide bond, and their selective incorporation into peptides attributes significant chemical and biological features. This study introduces an efficient synthesis of amidine-containing peptides by a copper-catalyzed, solid-phase-compatible multicomponent reaction (MCR), leveraging ketenimine intermediates that are generated in situ. Through the reaction of sulfonyl azides with terminal alkynes and a wide variety of amines, we establish the robust on-resin synthesis of delta/epsilon-amidine amino acids, arginine isologues, fluorescently labeled peptides, drug-peptide hybrids, and PEGylated derivatives. This strategy notably supports a wide range of peptide modifications, including side chain alteration, amine functionalization, and peptide macrocyclization through both backbone and side chain groups, as well as incorporating aromatic scaffolds into the peptide backbone. The methodology demonstrates broad substrate tolerance, compatibility with peptide chemistry protocols, and access to complex motifs, including pharmacophores and imaging tags, all within a single reaction platform. Our results underscore the synthetic versatility and functional applicability of ketenimine-based MCRs for advanced peptide modification, expanding the chemical space of peptide medicinal chemistry and therapeutics.
Keywords: Amidines; multicomponent reactions; peptide modification; Peptide-small molecule hybrids; Solid phase peptide synthesis

Peptide functionalization with dithioate and trithioate groups: A CS2-mediated solid-phase approach - Shinde, Dinesh R.; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Organic Letters, 2025)
The dithiocarbamate group is an important class of compounds whose presence in small molecules and peptides leads to antimicrobial, anticancer, and enzyme inhibition properties. This study introduces an efficient and selective method for incorporating dithioate and trithioate moieties into amino acids and peptides using CS2 chemistry under mild conditions. Utilizing a N,N-diisopropylethylamine (DIPEA)-CS2-benzyl chloride system, we achieved modifications at the N-terminal amines and the side chains of Lys and Cys residues through solid-phase peptide synthesis (spps). The method exhibits excellent yields and broad compatibility with diverse amino acids, their protection groups, peptide chemistry reagents, and varied peptide sequences. Notably, the successful incorporation of trithioate groups into peptides via cysteines, reported here for the first time, expands the functional repertoire of peptide chemistry, offering new possibilities for peptide-based drug design and related applications.

Peptide-triazolobenzodiazepine hybrids: a catalyst-free on-resin strategy to build complex therapeutic motifs into peptides - Kamble, Sandip Sushila Mohan; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Chemistry-A European Journal, 2025)
The merger of peptide and heterocyclic chemistry presents significant opportunities for enhancing the structural and functional diversity of therapeutic agents. In this study, we introduce a streamlined on-resin method to modify peptides at the N-terminus amines and the side chain amines of Lys/Orn amino acids by incorporating the biologically active triazolobenzodiazepine scaffold. In the presented solid-phase peptide synthesis (SPPS), the triazolobenzodiazepine core is formed on-resin through a combination of N-alkylation, amide bond formation, and an alkyne-azide 1,3-dipolar cycloaddition, of which the latter two happen as a single-step one-pot reaction- proceeding under mild conditions without metal catalysts. This protocol tolerates a wide variety of amino acids and functional groups, providing a versatile method for synthesizing peptide-triazolobenzodiazepine hybrids. Using orthogonal protection group strategies, we further demonstrate the method's adaptability for two site modifications in peptides involving both the N-terminus and Lys side chain amines. These modifications enhance the scope of ``peptide medicinal chemistry'' by creating multifunctional peptides with potential therapeutic applications. The method's compatibility with SPPS, room temperature conditions, and elimination of metal catalysis make it an efficient and powerful tool for peptide modification.
Keywords: hybrid peptides; peptide chemistry; peptide modification; spps compatibility; triazolobenzodiazepines

Nonpolar graphene oxide (GO-NP): a heterogeneous liquid crystalline alignment medium for anisotropic NMR in nonpolar organic solvents - Jatheendranath, Sandesh Chickmagalur; Deshpande, Sudhindra H.; Marelli, Udaya Kiran (Materials Chemistry Frontiers, 2026)
This study reports the development of a novel nonpolar variant of graphene oxide (GO-NP) as a heterogeneous NMR alignment medium for less polar organic solvents such as CDCl3. GO-NP was obtained through a stepwise derivatisation of polar GO with C10 and C18 alkyl amines, incrementally enhancing its dispersive character. The resulting doubly functionalised GO-NP exhibits liquid crystalline properties in CDCl3, enabling anisotropic NMR characterisation of small molecules. This represents the first GO-based system effectively suitable as a heterogeneous, dispersive alignment medium for nonpolar solvents, facilitating RDC investigations with background-free NMR spectra and complete analyte recovery.